A Conceptual Model of Knowledge Transfer and Acquisition through Arm's length Relationships - an Enterpreneurship Perspective - Geneste, Louis (Academy of World Business, Marketing and Management Development, 2006)
This paper develops a conceptual model of knowledge transfer and acquisition by small entrepreneurial firms through the arm’s length relationships they experience with their clients. Traditional interorganisational research has focussed on the more collaborative arrangements such as strategic alliances and joint ventures. Because of their lack of resources, many small firms are unable to enter such alliances. Instead, many of the small firm relationships tend to be arm’s length in nature, an area overlooked by researchers as a potential source of knowledge for the firm. Factors that contribute to knowledge transfer and acquisition in arm’s length relationships are also discussed.